Study of a new biocoagulant/bioflocculant mixture based on Boscia senegalensis seeds powder and Aloe vera leaves extract for the treatment of raw water intended for human consumption in rural areas of Sub-Saharan Africa - Konkobo, Frédéric Anderson; Diao, Mamounata; Ouédraogo, Elisabeth Rakisewendé; Barry, Poussian Raymond; Santara, Balamoussa; Zongo, Sandrine; Roamba, Noëlle Edwige; Dakuyo, Roger; Sanou, Abdoudramane; Kaboré, Kabakdé; Bazié, David; Savadogo, Paul Windinpsidi; et al. (Frontiers in Water, 2024)
IntroductionThe research of natural and sustainable solutions to improve rural water quality in developing countries of Sub-Saharan Africa represents a major challenge. It is in this context that the aim of this study was to evaluate the efficacy of a biocoagulant/bioflocculant mixture based on Boscia senegalensis seeds powder and Aloe vera leaves extract for treating water intended for human consumption in rural areas.MethodsTo do this, 100 g of Boscia senegalensis seeds powder and 50 g of Aloe vera leaves extract were prepared separately as aqueous solutions in 1 L of distilled water, then applied, respectively, as biocoagulant for Boscia and bioflocculant for Aloe to raw water samples in jar tests. The quality of the treated water was evaluated, and compared with WHO standards of acceptability.Results and discussionExperimental results showed that the Boscia senegalensis biocoagulant (at 7 mL/L) initially reduced turbidity by 85% after 2 h of decantation. When combined with Aloe bioflocculant (at 0.4 mL/L), a 99% reduction was obtained after just 15 min of decantation. Quality control of the water treated with this biocoagulant/bioflocculant mixture showed perfect compliance of physicochemical parameters with WHO standards, and almost total elimination of pathogenic microorganisms. These results demonstrate the effectiveness of this new Boscia/Aloe mixture in the rapid potabilization of raw water intended for human consumption. However, prolonged storage of water treated with the Boscia/Aloe mixture at room temperature may lead to further bacterial proliferation due to the remaining organic matter. To avoid this problem, additional disinfection methods such as boiling, SODIS (Solar Disinfection) method or sand filtration are recommended for prolonged storage of treated water. Ultimately, the adoption of this environmentally-friendly biotechnology could not only improve public health, but also empower local communities in Sub-Saharan Africa by providing them with a local and effective methodology for tackling the growing challenges associated with access to drinking water.